Bench-scale composting of newsprint sludge from a recycled paper mill - Naraval, Jose N. (Animo Repository, 2004)
This study is conducted to apply composting as an alternative sludge management to a particular recycled paper mill in the country, chosen by ARRPET-DLSU as an industry research partner. Three bench-scale reactors were fabricated to investigate the compressive stress of a large-scale windrow. Three C:N ratios were investigated (105, 30 and 20) using combined chicken and duck litter as a nitrogen amendment. Moisture content and the amount of the inoculum added in the three reactors are held constant. It was found tht lower C:N ratios exhibited an improved composting performance compared to the nitrogen-amended feedstock (control). Lower C:N ratios attained higher maximum temperature. Nitrogen-treated feedstock has reached the thermophilic range and stayed between that range for about 7 to 8 days. No nitrogen treatment feedstock (control) stayed only in the mesophilic range for the entire course of composting. Composting time fell, as well, when C:N ratio is decreased. The reduction of the volatile solids increased by at least 77% and maximum mass reduction of 41.5% was achieved when C:N was decreased from the control to 20. C:N = 30 attained an increase of at least 67% in volatile solids reduction and a 38.2% loss of weight compared to the control. Although C:N = 20 showed the highest composting performance, the excessive nitrogen added in this treatment is not recommended in this study due to excessive liberation of ammonia gas during and after composting. If composting will be carried out in large-scale processes, odor problems might arise. Chemical analysis of the compost reveals that most of the chemical parameters passed the standards established by the Fertilizers and Pesticides Authority (FPA). Although C:N ratio and moisture content are slightly higher than what was established by the regulatory agency, increased retention time of the compost would bring down these values to the specified standards. However, microbial analysis shows the high presence of pathogens in the nitrogen-amended compost that may create another environmental problem if used in the soil for plant application. Further work is needed to investigate other applications of the compost to lessen environmental problems.